IV Brazilian Consensus on Rhinitis - an update on allergic rhinitis, - Sakano,Eulalia (2018)
Abstract Introduction The guidelines on allergic rhinitis aim to update knowledge about the disease and care for affected patients. The initiative called "Allergic Rhinitis and its Impact on Asthma", initially published in 2001 and updated in 2008 and 2010, has been very successful in disseminating information and evidence, as well as providing a classification of severity and proposing a systemized treatment protocol. In order to include the participation of other medical professionals in the treatment of allergic rhinitis, it is important to develop algorithms that accurately indicate what should and can be done regionally. Objective To update the III Brazilian Consensus on Rhinitis - 2012, with the creation of an algorithm for allergic rhinitis management. Methods We invited 24 experts nominated by the Brazilian Association of Allergy and Immunology, Brazilian Association of Otorhinolaryngology and Head and Neck Surgery and Brazilian Society of Pediatrics to update the 2012 document. Results The update of the last Brazilian Consensus on Rhinitis incorporated and adapted the relevant information published in all "Allergic Rhinitis and its Impact on Asthma" Initiative documents to the Brazilian scenario, bringing new concepts such as local allergic rhinitis, new drugs and treatment evaluation methods. Conclusion A flowchart for allergic rhinitis treatment has been proposed.